Techno-Economic Analysis of Hybrid Systems as a Solution for Electricity Supply during the Dry Season at the Bakaru Run-of-River Hydropower Plant - Febri, Zamharir Aditya; Indianto, Mohammad Akita; Tobing, Sheila (Journal of Materials Exploration and Findings, 2026)
Within the South Sulawesi power system (Sulbagsel), the Bakaru Hydro Power Plant serves as a key facility expected to provide consistent and reliable electricity supply. However, since the Bakaru plant operates under a Run of River scheme, its energy output is highly dependent on river discharge rates. In 2024, a significant decrease in water flow was recorded between August and October, which led to a drastic reduction in power generation. To address this challenge, a hybrid energy system is proposed to ensure continuous load coverage, particularly during the dry season. The optimal configuration of this hybrid system was modeled and simulated using HOMER Pro software. The simulation results indicate that a combination of the existing Bakaru Hydro Power Plant 126 MW, Solar PV 100 MWp, BESS of 24 MWh, and a steam-gas power plant 80 MW can effectively fulfill the annual electricity demand. The proposed hybrid system yields a total annual energy output of 862,719.29 MWh, which exceeds the actual load demand by 33.6% (equivalent to 290,164.45 MWh). This energy surplus can be strategically allocated to accommodate seasonal loads or projected demand growth. From an economic standpoint, the configuration demonstrates a Net Present Cost (NPC) of USD 934 million, with Levelized Cost of Electrictricity (LCOE) of USD 0.0583 per kWh. Furthermore, the project displays promising investment viability, achieving an Internal Rate of Return (IRR) of 31.57% and a payback period of four years and a projected Net Present Value (NPV) of USD 715,487,322.